The Influence of Workplace Facilities and Training on Motivation and its Impact on Employee Performance at the One-Stop Administration System in Jambi City - Marantikasari, Shanti; Suryani, Arna; Akbar, Ali (Journal of Accounting and Finance Management, 2025)
This study aims to analyze the effect of workplace facilities and training on motivation and their impact on employee performance at the One-Stop Administration System (Samsat) in Jambi City. The research adopts a quantitative approach using a survey method. The population consists of all 80 Samsat employees in Jambi City, with the sample determined using a census method so that the entire population served as respondents. Data were collected through questionnaires that had been tested for validity and reliability. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS. The results show that workplace facilities have a positive and significant effect on motivation and employee performance, training has a positive and significant effect on motivation and employee performance, and motivation has a positive and significant effect on employee performance. Furthermore, motivation was found to mediate the effect of workplace facilities and training on performance. These findings indicate that improving employee performance can be achieved by enhancing workplace facilities, increasing the quality and quantity of training, and strengthening employee motivation. This study provides practical implications for Samsat Jambi City management to prioritize the provision of adequate infrastructure and relevant training programs to support the achievement of organizational goals.